1966
DOI: 10.5006/0010-9312-22.6.178
|View full text |Cite
|
Sign up to set email alerts
|

Surface Chemical Factors in the Stress-Corrosion Cracking off Alpha Brass

Abstract: Stress corrosion cracking of alpha brass in ammonia solutions containing copper-ammonia complexes is most rapid in the pH range 6 to 7, where weight loss corrosion is insignificant, Linear relationships were found for (a) log 1/tc (tc = cracking time) vS log Cu++ (initial copper concentration) and (b) l/tc vs 1/T (T = absolute temperature). Oxygen appears necessary for general corrosion and cracking at pH values above 8. Rapid cracking is interpreted in terms of a drastic surface free energy dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
4

Year Published

1968
1968
2005
2005

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 48 publications
(21 citation statements)
references
References 0 publications
3
14
0
4
Order By: Relevance
“…The surface attained a steady state during cycles number 5 and 7 at 293 and 313 K, respectively. This result can be attributed to the low dissolution process of the corrosion products, which leads to the rapid passivation of the surface at 293 K. X-ray diffraction analysis indicated that the films formed on brass were predominantly Cu 2 O and Zn 5 (OH) 8 Cl 2 H 2 O; this is consistent with the results reported previously for brass tested in tarnishing solutions [28][29][30] as well as in a marine environment [31]. The results reported previously indicated an increase in the corrosion rate with increase in temperature [32].…”
Section: Influence Of Temperaturesupporting
confidence: 92%
“…The surface attained a steady state during cycles number 5 and 7 at 293 and 313 K, respectively. This result can be attributed to the low dissolution process of the corrosion products, which leads to the rapid passivation of the surface at 293 K. X-ray diffraction analysis indicated that the films formed on brass were predominantly Cu 2 O and Zn 5 (OH) 8 Cl 2 H 2 O; this is consistent with the results reported previously for brass tested in tarnishing solutions [28][29][30] as well as in a marine environment [31]. The results reported previously indicated an increase in the corrosion rate with increase in temperature [32].…”
Section: Influence Of Temperaturesupporting
confidence: 92%
“…The composition conformed approximately to that recommended earlier by Mattsson (18), and by Johnson and Leja (14) for producing minimum failure times; it consisted of 0.05M CuSO4 and 1.0M (NH4)eSO4 of pH 6.5 adjusted using NH4OH. The composition conformed approximately to that recommended earlier by Mattsson (18), and by Johnson and Leja (14) for producing minimum failure times; it consisted of 0.05M CuSO4 and 1.0M (NH4)eSO4 of pH 6.5 adjusted using NH4OH.…”
Section: Methodssupporting
confidence: 58%
“…4). Johnson and Leja (14) reported for 69.5% Cu-30.5% Zn brass in 0.04M Cu, 1.SM total NH3, pH 6.8 solution, a variable activation energy ranging from 4 to 11.5 kcal/mole. This value agrees with that of 9.9 kcal/mole reported by Pugh et aI.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Die Ammoniumionen schienen uns deshalb von besoiiderem Interesse, weil sie liisliche Kupfer-Ammoniuinkomplexe bilden koiineii uiid aderdeiii Ammoniumioneii in neutralen uiid alkalischen Losungen die Ursaclie von Korrosioiis-KiRbildung a n Messing sind (29)(30)(31)(32)(33)(34)(35)(36) 3.31 C~77Zii21.412As'~' (2) 76,2 2,11 3,23…”
Section: Die Korrosion Von Messing In Ammoniumchloridlosungenunclassified